Beleza e carreira no Brasil: o significado da beleza para jovens executivas e seu papel no mercado de trabalho - Gomes, Juliana Penha (2010)
This paper addresses two topics of interest and prominence in the life of modern woman: beauty and career. For consistent analysis, we chose to use qualitative methodology, recommended for studies in which the phenomena are related to human beings and their relationships in society. The research was divided into two stages: a review of the literature related to female identity, beauty and consumer behavior and in-depth interviews with six young executive women working in the city of São Paulo. During the interviews, the main focuses were the meaning of beauty, its role in the Brazilian labor market and cnsumption habits of beauty. In the final step, we performed a quantitative pre-testing with some recruiters, also from São Paulo, who pointed out some trends. The theoretical basis, joint with the findings of the interviews, provided the development of research propositions and identified variables for the development of a model. From the study it was found in practice that: I. Beauty is valued in the Brazilian labor market, influencing the perception of competence; II. There is the stereotype of the successful executive in the country, combining both physical and behavioral characteristics, III. Gender stereotypes are part of the young executive life, making the female identity multiple and generating overload, IV. Lack of female role models, due to the lack of women in executive positions and also the high expectations, V. And finally, the consumption of beauty is emphasized, as for desire satisfaction or self-image construction, generating a market segment that consumes a lot, and influence other to consume.